2005
DOI: 10.1128/jb.187.20.7138-7145.2005
|View full text |Cite
|
Sign up to set email alerts
|

Global Transcriptome Analysis of Shewanella oneidensis MR-1 Exposed to Different Terminal Electron Acceptors

Abstract: To gain insight into the complex structure of the energy-generating networks in the dissimilatory metal reducer Shewanella oneidensis MR-1, global mRNA patterns were examined in cells exposed to a wide range of metal and non-metal electron acceptors. Gene expression patterns were similar irrespective of which metal ion was used as electron acceptor, with 60% of the differentially expressed genes showing similar induction or repression relative to fumarate-respiring conditions. Several groups of genes exhibited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
167
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 206 publications
(176 citation statements)
references
References 53 publications
8
167
1
Order By: Relevance
“…These proteins have a central function in anoxic electron transfer to a multitude of different electron acceptors. Several researchers already showed a coexpression of several c-type cytochromes at the level of the transcriptome (Beliaev et al, 2005;Gralnick et al, 2005). Nevertheless, it is unknown what this coexpression really infers regarding the physiology of the organism and the biochemistry of electron transfer to the arsenal of electron acceptors that S. oneidensis is able to reduce.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These proteins have a central function in anoxic electron transfer to a multitude of different electron acceptors. Several researchers already showed a coexpression of several c-type cytochromes at the level of the transcriptome (Beliaev et al, 2005;Gralnick et al, 2005). Nevertheless, it is unknown what this coexpression really infers regarding the physiology of the organism and the biochemistry of electron transfer to the arsenal of electron acceptors that S. oneidensis is able to reduce.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it has to be assumed that proteins like MtrA can diffuse through the periplasm or that additional redox proteins mediate electron transfer through the periplasm. The genome of S. oneidensis MR-1 contains the genetic information for 27 c-type cytochromes that are putatively localized to the periplasm, and a surprising number of them is expressed in high concentration immediately after conditions change from oxic to suboxic (Beliaev et al, 2005;Romine et al, 2008;Gao et al, 2010). Nevertheless, it is not known which of these cytochromes are necessary to bridge the periplasmic gap between CymA and the outer membrane.…”
Section: Introductionmentioning
confidence: 99%
“…for 5 min at 4 1C, flash frozen in liquid nitrogen and stored at À 80 1C. Total RNA extraction was carried out according to previously published protocols (Beliaev et al, 2005). The quality and integrity of the RNA was assessed on an Agilent 2100 Bioanalyzer and only samples with integrity numbers between 8 and 10 were selected for further analysis (Schroeder et al, 2006).…”
Section: Rna Isolation and Sequencingmentioning
confidence: 99%
“…The observed increase in ribosomal abundance at higher potentials for both S. oneidensis and G. sulfurreducens, is supported by a study that suggests a direct relationship between ribosomal gene expression and the potential of electron acceptors [99], after reanalysing data from a previous study [193]. However, later it was suggested that S. oneidensis ribosomal expression may rather be related to EET and not electrode potential [99].…”
Section: 2)mentioning
confidence: 50%
“…In addition, a correlation study of previous research on S. oneidensis [193] looked at the ribosomal protein expression levels of three different electron acceptors: iron, cobalt and manganese [99]. There was found to be a direct relationship between ribosomal gene expression and the redox potential of each of the solid electron acceptors.…”
Section: Ribosomal Proteinsmentioning
confidence: 99%